POLLINATION ECOLOGY, BREEDING SYSTEMS AND SEED DISPERSAL IN PASSIFLORA FOETIDA L. (PASSIFLORACEAE), A PERENNIAL HERBACEOUS CLIMBER WEED IN SOUTHERN PARTS OF ANDHRA PRADESH, INDIA.: POLLINATION ECOLOGY OF PASSIFLORA FOETIDA L. (PASSIFLORACEAE). - RAO M. MALLIKARJUNA (BIOTROPIA, 2023)
Passiflora foetida L. (Passifloraceae) is an herbaceous climber weed; grows up to 1.5 - 6.5m tall occur in riverbeds, wastelands, forest floors, crop fields, and roadsides, ascend about 4 to 10 m (13 to 32 feet) tall, exhibit peak flowering in July to December; produce white flowers marked with a ring of radially oriented purple streaks nectar guide, the flower opens along with sunrise and closes the same day noon. It exhibits three kinds of stigma positions in the same plant with different frequencies which determined the fertility rate of flower 1. Stigma below the anthers 64% (fully curved), 2. Stigmas above the anthers 16% (no curvature), 3. Stigmas above anthers 20% (partially curved). P. foetida flower shows both self-pollination and Cross-pollination. Xylocopa latipas sp. visits the flowers frequently among all of the forages and the Stigmas curved below the anthers produce height fruit set (68%) and seed set (82.14%). The fruits and seeds spread far destinations by animals (Zoochory). It cultivates in agricultural fields for their ornamental flowers, edible fruits, and pharmaceutical uses. The present study explored ecological importance, reproductive ecology and the pollinator interaction of the plant.